White croaker (Micropogonias furnieri) paleodistribution in the Southwestern Atlantic Ocean. An archaeological perspective - Scartascini, Federico Luis (2013)
This paper presents strong and well dated evidence of the presence of Micropogonias furnieri in areas that are currently out of distribution. This evidence comes from hunteregatherer archaeological sites along the north Patagonian coast (Argentina). Our results allow us to determine a change in the spatial distribution of M. furnieri during the Holocene, which are possibly linked to biogeographic changes in a set of species at regional level. Finally we discuss the potential for archaeological evidence in the service of spatial and biogeographic studies of different species.